Astrology, palmistry and metoposcopy as a complement to the physiognomic image of the soul in the philosophy of Marin Cureau de La Chambre - Stegliński, Tomasz (Hybris, 2022)
The article entitled: Astrology, Palmistry and Metoposcopy as a Complement to the Physiognomic Image of the Soul in the Philosophy of Marin Cureau de La Chambre aims to present the views of a little-known French doctor and philosopher in Poland. Living and creating in seventeenth century, de La Chambre is a representative of post-Cartesian philosophy. His studies concern the physiognomic image of the human psyche. The article briefly presents the content of the main works of this author, which include Les Characteres des passions, vols. 1–4, Paris1662 and L'art de connoistre les hommes, Amsterdam 1660. It is in these books that the scholar presents the principles of getting to know people, resulting from the combination of medical knowledge and the analysis of emotions in a person. In the second part, the article presents the content of two letters that de La Chambre attached to L'art de connoistre les hommes. These are: Discours sur les principes de la chiromance (Dissertation on the principles of palmistry) and Discours sur les principes de la metoposcopie (Dissertation on the principles of metoposcopy). The scientist studies the utility of these pseudo-sciences for the purposes of medicine so that, together with physiognomy, they can replenish the necessary knowledge not only about the behavior of people, but about the traits of their character, as well as the fate with reference to the incidence of various diseases. The article presents a less popular and familiar part of the knowledge in the field of the development of post-Cartesian medical philosophy in France in the seventeenth century.